Assessments of world and national level wrestling teams at a pre world championship competition: hydration, body composition and body mass alterations - Kutlu, M.; Demirkan, E.; Özbek, M. E. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: This study examined the changes in hydration status, body composition and body mass alterations during the camping period a pre world championship, World (N.=14) and National (N.=38) senior wrestlers (N.=52) preparing for the World Championships.